The influence of corporate income taxes on investment location: Evidence from corporate headquarters relocations - CHOW, Travis (Institutional Knowledge at Singapore Management University, 2022)
This study examines the effects of jurisdictions’ corporate taxes and other policies on firms’ headquarters (HQ) location decisions. Using changes in state corporate income tax rates across time and states as the setting, we find that a one-percentage-point increase in the HQ state corporate income tax rate increases the likelihood of firms relocating their HQ out of the state by 16.8%, and an equivalent decrease in the HQ state rate decreases the likelihood of HQ relocations by 9.1%. Exploiting the unique tax policy features within the state apportionment system lends strong support to the interpretation that taxation drives this effect. Our analyses also demonstrate that state income tax features affect the destination of the HQ move. We contribute to the literature on corporate decision making by showing how state income taxation affects a real corporate decision that has significant economic consequences for the company and the state.